Spiritual care in the intensive care unit. Is it already a reality?: an integrative review - Alessandre Carvalho Junior; Adriane Maria Netto de Oliveira; Camila Daiane Silva; Diéssica Roggia Piexak (Einstein (São Paulo))
ABSTRACT Introduction Spirituality has emerged as a phenomenon of interest in various global contexts. The adoption of spirituality as a fundamental aspect of healthcare remains underexplored, especially in critical environments such as intensive care units. Objective To identify strategies for incorporating spiritual care into adult intensive care environments through an integrative literature review. Methods An integrative review was conducted using the Embase, Web of Science, Medline/PubMed, PsycINFO, LILACS, and Cochrane Central databases. Twenty-one studies published in English, Spanish, or Portuguese over the last 10 years were selected. Results Different approaches to spirituality were identified, including training implementation, individual interviews, meetings, educational programs, and practices involving healthcare professionals. Conclusion Spirituality in the intensive care environment has been a growing reality in recent years through efforts aimed at helping healthcare professionals integrate spirituality into the care provided in clinical practice. Individual interviews were the primary strategy for incorporating spiritual care in intensive care unit settings. Questionnaires were used to support these interviews, and the frequency and duration typically involved a single session, ranging from 15 to 60 min.